A study of official media outlets of Muslim Brotherhood group and Freedom and Justice Party in Egypt - Ibrahim, Shaimaa Mostafa (AUC Knowledge Fountain, 2013)
Before the 25th of January revolution in Egypt, the types of Islamic media, such as Internet websites and television satellite channels, were focusing only on the education and interpretation of Islam. Furthermore, these Islamic media were not used as a tool to propagate for the political ideologies of Islamic movements. On the other hand, after the revolution, the Islamic media, specifically, television satellite channels start to act as a forum for the politics of the Islamists groups in Egypt. The main focus of this study aims at studying and examining the official media outlets of Muslim Brotherhood group and Freedom and Justice Party. In addition, this study aims to analyze how the Muslim Brotherhood group and Freedom and Justice Party use their official mass media to represent their visions and ideologies to the Egyptian public. The theoretical framework of this research is the Agenda Setting Theory with the focus of media Priming. This study examined how the official media outlets of Muslim Brotherhood group and Freedom and Justice Party apply the agenda setting through highlighting specific issues and ignoring other issues. This study is a content analysis of three official media outlets of Muslim Brotherhood group and Freedom and Justice Party which are: Misr 25 television satellite channel, Ikhwanonline Internet website, and Freedom and Justice Newspaper. The sample is non-probability sampling which is a Purposive Sample, and the sampling period is one composite week. This study consists of analyzing 7 issues of Freedom and Justice Newspaper, 7 days of Ikhwanonline Internet website, and a total of 63 hours of 18 television programs and talk shows of Misr 25 television channel. The findings of the study concluded that the Muslim Brotherhood group and Freedom and Justice Party use their official media outlets which are Misr 25 television channel, Ikhwanonline Internet website and Freedom and Justice Newspaper to convey their Islamic ideologies in different fields such as political issues, economic issues, social issues and religious issues to the masses in Egypt. Additionally, the findings of this research are in agreement with the theory of agenda setting theory because the official media outlets of Muslim Brotherhood group and Freedom and Justice Party highlight specific issues through repeating these issues; on the other hand, they have little coverage of other important issues. Regarding the media priming, the official media outlets of Muslim Brotherhood group and Freedom and Justice Party have some news that are salient than others. Furthermore, a lot of issues in the mass media of Muslim Brotherhood group and Freedom and Justice Party are obtrusive issues which mean that the audiences have a direct experience with these issues; therefore, the agenda setting effect may be low.